The Manasseh Hill country survey / Volume 6 The Eastern Samaria shoulder, from Nahal Tirzah (Wadi Far'ah) to Ma'ale Ephraim junction - Bar, Shay (The Manasseh Hill Country survey, 2021)
"The book presents the results of a complete detailed survey of the eastern region of Samaria, mainly the Eastern Samaria Shoulder, from Nahal Tirzah (Wadi Far'ah) to Ma'ale Ephraim Junction within the territory of Israel/Palestine. It is Volume 6 of the Manasseh Hill Country Survey publications. This project, in progress since 1978, and covering 2500 sq. km, is a thorough, metre-by-metre mapping of the archaeological-historical area between the River Jordan and the Sharon Plain, and between Nahal 'Iron and the north-eastern point of the Dead Sea. This territory is one of the most important in the country from the Biblical and archaeological view; and the survey is a valuable tool for scholars of the Bible, archaeology, Near Eastern history and other aspects of the Holy Land"